[Original in Portuguese] The impact of recurring urinary infections on the quality of life of women in outpatient care in Brazil - Garcia Lourenção , Luciano; Flores de Oliveira , Jacqueline; Carraro-Eduardo , José Carlos; Machado Homem , Giovani; Augusto Faria, Carlos (Población y Salud en Mesoamérica, 2024)
Objective: To evaluate the impact of recurring urinary infections on the quality of life of women in outpatient care. Method: Observational, descriptive, and analytical study with 98 women attended in the outpatient clinic of a public teaching hospital in Niterói, Rio de Janeiro, Brazil. 49 of these women had recurring urinary infections, confirmed by urine cultures, with no complications; 49 had no recurring urinary infections, and the two groups were matched for age. Quality of life was evaluated using the Brazilian version of the World Health Organization's abbreviated questionnaire WHOQOL-Bref. Results: The quality of life of women with urinary tract infections was more compromised in the physical (p = 0.007) and psychological (p = 0.038) domains. These women also presented a lower self-assessment of quality of life (p = 0.002) when compared to the control group. Women with recurring urinary infections presented significantly lower mean scores than the control group in the facets Energy and fatigue (p = 0.003), Positive Feelings (p = 0.014), Self-esteem (p = 0.040), Dependence on medicinal substances (p = 0.029), Negative Feelings (p = 0.023), and Recreation/leisure activities (p = 0.041). Conclusion: Recurring urinary tract infections have an impact on the quality of life of women, especially in the Physical and Psychological domains, being a significant problem for women, health workers, and the health system as a whole.